(untitled) (Global Journal of Management and Business Research, 2019)
This study aims to describe the influence of job satisfaction, organizational justice and employee empowerment towards organizational commitment to Amanusa Hotel employees in Nusa Dua. Samples taken as many as 60 people with proportional random sampling. The data was collected by distributing questionnaires using a 5- point Likert scale to measure 42 statement items. The analysis technique used is Multiple Linear Regression Analysis. These results show that job satisfaction has a positive and significant effect on organizational commitment. Organizational justice has a positive and significant impact on organizational commitment. Empowerment has a positive and significant impact on organizational commitment. Parties should always pay attention to job satisfaction, organizational justice and employee empowerment so that employees will have a high commitment to the organization.